PELAKU BUDAYA PINGGIRAN DAN EKSPRESI: MEMBACA SENIMAN SUMATERA - Wannofri Samry (Diakronika, 2017)
There are two problems faced by the actors of culture of periphery, both power of capitalisms tend to follow market and dominate the power of discourse in center of politics. Thus, the consequences of these problems are stagnation of artists’ creativity at periphery area. Although the actors at periphery express their ideas with some innovations, they are not touched or do not want to be touched. As far as the Indonesian history centralizes or refers to Jakarta, as a consequence, the actors of art-culture at periphery are eliminated. Therefore, the expression of periphery area (Sumatera) is filtered by central dominator of culture who has lived in center of the state. The Actors in periphery are defined, influenced but can not be influenced and do not have freedom in creating arts. The actors at periphery are forced to express the pressure of ideology and market that available in center of power. This paper is aimed at elaborating the condition of artists in Sumatera in the last two periods. How did they response to the centralistic and dominate power? What were changes of orientation and activity style of Sumatera artists community life?